DESIGN OF A KIDS ART SPACE AS A MEDIUM FOR DEVELOPING EARLY CHILDHOOD CREATIVITY IN EARLY CHILDHOOD EDUCATION (PAUD) INSTITUTIONS IN GORONTALO CITY - Sutisna, Icam; Juniarti, Yenti; Zakaria, Sri Indrawati; Maruwa, Nurhalimawati; Gani, Amelia; Mohu, Alisyah; Amara, Salsabila (PERSPEKTIF: Journal of Social and Library Science, 2025)
This research aims to design a Kids Art Space as a medium for stimulating creativity in early childhood education institutions (PAUD) in Gorontalo City. The research background is based on the limited availability of creative space facilities, which results in children's art activities tending to be instructional and rigid. The method used was Research and Development (R&D) with a Design Thinking approach, encompassing the stages of empathy, definition, ideation, prototyping, and testing. Data were collected through participatory observation, in-depth interviews with educators, and a study of child ergonomics. The results of the study yielded a space design model that integrates flexible wet and dry activity zoning and the use of child-friendly modular furniture. The strength of this design lies in the incorporation of local Karawo motifs as ethno-pedagogical visual stimuli. The study's conclusions indicate that thematically designed Kids Art Space significantly enhances children's independence and courage to explore. This space acts as a "third teacher" facilitating fine motor and cognitive development. The implementation of this design is expected to become a standard reference for innovative PAUD facilities in Gorontalo City in supporting the Independent Curriculum.